A STUDY OF INTERACTION AND INTERACTIVE METADISCOURSE ON UKRAINE-RUSSIA CONFLICT NEWS ARTICLES - Annisa Nanda Putri; Tommy Hastomo; Muhammad Farhan; Kartika Yunaini (Journal of English Teaching, Applied Linguistics and Literatures (JETALL), 2023)
Abstract: Metadiscourse plays an important role in news article writing as it allows writers to express their feelings and ideas using language. The objective of this study is to investigate the usage of interactive and interactional metadiscourse markers in news articles about the conflict between Russia and Ukraine. The research design is descriptive and qualitative, based on the theory of interactive and interactional metadiscourse markers by Hyland (2005). Five news articles were selected from The New York Times' English news article website, published between November 9-18, 2022. Data was collected using document research and analyzed through document analysis. Results showed that all types of interactive and interactional metadiscourse were present in the news articles, except for booster. The most frequently used interactional metadiscourse was self-mention, accounting for 65%, while the most frequently used interactive metadiscourse was transition, accounting for 84.7%. The implications of the above research suggest that the use of interactive and interactional metadiscourse in news articles can enhance reader engagement and understanding of the content.